Impact of smoking on the social gradient in health expectancy in Denmark - Bronnum-Hansen, H. (BMJ Group, 2004)
Study objective: Health expectancy is arrived at by dividing life expectancy into average lifetime in different states of health. The purpose of the study was to estimate health expectancy among never smokers and smokers in groups at high, medium, and low educational levels in Denmark. Design: Life tables for never smokers and smokers with a high, medium, and low educational level were constructed on the basis of Statistics Denmark registers and combined with data from the Danish Health Interview Survey 2000. Health expectancy was calculated by Sullivan's method. Main results: Life expectancy at age 30 differs on average by 8.5 years between never smokers and heavy smokers. Expected lifetime in self rated good health was 39.4 years for a never smoking man corresponding to 82.0% of the rest of his life. For male lifelong heavy smokers these figures were reduced to 27.3 years and 69.2%. The proportion of expected lifetime in self rated good health was 89.5% and 71.3% among male never smokers and lifelong heavy smokers with a high educational level, respectively; and the proportion among male never smokers and heavy smokers with a low educational level was 73.4% and 63.6%, respectively. Similar results were seen as regards expected lifetime without longstanding illness. For women the social gradient in health expectancy was intensified among smokers. Conclusions: Within each educational group smoking reduces expected lifetime in a healthy state. The social gradient in health expectancy cannot be explained by a reverse social gradient in smoking prevalence.